Chapter Грамматикализация глагольного вида в резьянском диалекте: исконно славянская и романская лексика* - Steenwijk, Han (Biblioteca di Studi Slavistici, 2017)
This paper discusses the morphological means used to express verbal aspect in Resian. A marked difference can be observed between the native Slavic verbal lexicon, which mainly shows prefixation, thereby creating perfective forms, and that of Romance origin, where prefixation is almost completely absent and suffixation abounds, thereby creating imperfective forms.